Performance of taro under poplar based agroforestry system in the Western Himalayas - Singh, Rajat; Lavania, S.K.; Sah, V.K.; Singh, Manendra (Indian Journal of Agroforestry, 2021)
Taro (Colocasia esculenta L. Schott) is a staple food crop. The growth and productivity of the taro differ with age of plantation and nature of tree–crop interaction. The present study was carried out to evaluate the vegetative growth and yield of taro under poplar (Populus deltoides Bartr. Ex Marsh) based agroforestry system and taro as a sole crop at Govind Ballabh Pant University of Agriculture and Technology, Uttarakhand. The experiment was conducted by selecting 10 germplasms of taro randomly with 5-year old poplar plantation and a controlled experiment (without poplar) using a Factorial Randomized Block Design with three replications. The results revealed that all the germplasms evaluated performed better in terms of growth and yield parameters under sole cropping (open condition) as compared to poplar based agroforestry system. The study revealed that yield of taro germplasm was significantly lower under poplar plantation. The germplasm PA-16 produced maximum yield (145.74 q ha-1) under poplar based agroforestry while germplasm PA-12 gave higher yield under sole cropping (364.10 q ha-1).